Determinan Kinerja Karyawan Bank Swasta Di Kota Medan - Chandra, Dody Salden (Balance : Jurnal Akuntansi dan Manajemen, 2022)
This study aims to determine and analyze the influence of talent management, multiple role conflicts, and job stress on the performance of private bank employees in Medan. This research is associative, namely research that connects two or more variables to see the effect of these variables. The population in this study were all employees of the Medan Branch of Private Banks. The number of samples in this study was 140 people with a proportional random sampling technique. The data used in this study are primary data and secondary data. analysis technique using multiple linear regression analysis, with the help of SPSS. The results of this study indicate that Talent Management, Multiple Role Conflict, and Job Stress simultaneously have a significant effect on the performance of private bank employees in Medan. The results of the partial test show that Talent Management has a positive and significant effect on the Performance of Private Bank Employees, Multiband Role Conflicts have a significant effect on Performance. Private Bank Employees in Medan and Job Stress have a significant effect on the Performance of Private Bank Employees in Medan